Discovering time-trends of the German populations exposure to contaminants by analysis of human samples of the German Environmental Specimen Bank (ESB). (1st December 2018) - Göen, Thomas; Lermen, Dominik; Hildebrand, Jörg; Bartel-Steinbach, Martina; Weber, Till; Kolossa-Gehring, Marike
Highlights: German ESB archives biological material of about 500 young adults annually since 35 years. Real-time monitoring (RTM) of HBM parameters in freshly taken samples reveals exposure situation directly. Archived samples can be used for retrospective analysis of new appearing contaminants. Human biomonitoring (HBM) data of the German ESB identify long-term trends in exposure. German ESB is a valuable tool to reveal necessity and success of regulatory measures. Abstract: The German Environmental Specimen Bank (ESB) is a monitoring instrument of the German Federal Ministry for the Environment, Nature Conservation and Nuclear Safety. The permanent biobank facility is run since 1981 containing environmental and human samples from Germany. All samples are collected according to standard operating procedures (SOP). An standardized annual collection of human samples at four different regional sites of the country has been established since 1997. Routine sampling is done once a year, recruiting healthy non occupationally exposed students aged 20–29 years, in an equal gender distribution. The number of participants recruited is approximately 120 students per site and year. Directly after the annual sampling process, the human samples are analyzed for selected environmental chemicals. The time-trends of lead in blood, mercury and pentachlorophenol in 24 h-urine and polychlorinated biphenyls in plasma demonstrated a decrease of exposure during the last two decades by about 40–90 percent. In parallel retrospective studies using cryo-archived samples revealed increasing time trends of emerging chemicals used as substitutes for regulated toxicants. The data demonstrates the great relevance of the ESB for the health related environmental monitoring and shows the importance of human biomonitoring as a tool in information based policy making.